Are Employees Committed to Diversity at Work and in Their Personal Lives? The Role of Organizational Antiracist Signaling Following a Racial Injustice Event - Volpone, Sabrina D.; Casper, Wendy J.; Wayne, Julie Holliday; White, Marla L. (Human Resource Management, 2025)
ABSTRACT Research on corporate sociopolitical activism (CSA) is in its infancy, and more research is needed to examine its effects on employees. We draw from the tenets of Signaling Theory to develop and test a model of how organizations' antiracist signaling after a racial injustice event, as a form of CSA, communicates that racial justice is valued sincerely by organizations, and in turn, motivates employee commitment to diversity—both at work and in their personal lives. We also explore boundary conditions (i.e., climate for inclusion, employee race) of this relationship. We test our model with data collected from 367 employees (37.6% Black, 62.4% White) across 4‐time waves, each 1 month apart, using a mixed‐methods (quantitative and qualitative) approach. Results suggest that organizations are viewed as most sincere when they engage in signaling that includes both words (i.e., releasing a statement) and actions (e.g., hiring a diversity officer) relative to when they don't engage in these words and/or actions. Moreover, when organizations signaled a sincere commitment to antiracism with both words and actions, employees were more committed to diversity at work and in their personal lives, though actions taken by the organization were especially important. Moreover, a strong climate for inclusion reduced the need for actions, while a weak climate for inclusion increased the need for a statement. Theoretical, research, and practical implications are discussed.